2013
DOI: 10.1007/s13592-013-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering strategies in the red mason solitary bee—physiological correlates of midgut metabolic activity and turnover of nutrient reserves in females of Osmia bicornis

Abstract: -The catabolic activity of midgut and the turnover of metabolic reserves in fat body and hemolymph was studied during 7 months of overwintering period (September-March) in the European solitary red mason bee Osmia bicornis L. (Hymenoptera: Megachilidae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
(47 reference statements)
4
16
0
2
Order By: Relevance
“…This pattern suggests that diapausing S. crassipalpis pupae utilize fat stores as the primary metabolic fuel during the first half of diapause, and other substrates, perhaps carbohydrates or proteins, in the second half of diapause. We reported observing a similar situation in over-wintering O. bicornis females (Wasielewski et al 2013). At the beginning, in September, the highest level of free lipds in hemolymph was recorded.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This pattern suggests that diapausing S. crassipalpis pupae utilize fat stores as the primary metabolic fuel during the first half of diapause, and other substrates, perhaps carbohydrates or proteins, in the second half of diapause. We reported observing a similar situation in over-wintering O. bicornis females (Wasielewski et al 2013). At the beginning, in September, the highest level of free lipds in hemolymph was recorded.…”
Section: Discussionsupporting
confidence: 70%
“…Fat body extracts were injected in given concentration range through the ventral membrane into the hemocoel between the 6th and 7th abdominal tergites. After 24 h, 0.5 μL hemolymph was collected to determine the effect of the fat body extract on lipid content (Zöllner and Kirsch 1962;Wasielewski et al 2013). …”
Section: Hormonal Extracts and Hormone Injectionsmentioning
confidence: 99%
“…In fact, spirotetramat acts as lipid biosynthesis inhibitor . Lipid reserves accumulated during larval development are very important in Osmia spp., and depletion of the reserves affects both the wintering survival and the vigour of the bees after emergence (Sgolastra et al, 2011;Wasielewski et al, 2013). Because the difference in adult longevity between treated and control bees, was an average of 1 day, further studies are necessary to assess whether the observed effect is relevant in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many bee species undergo diapause at some point in their life cycle, including solitary bee species, such as Megachile rotundata (Fabricius), Nomia melanderi (Cockerell), Osmia rufa (Linnaeus), and Osmia lignaria Say (Hsiao & Hsiao, 1969;Bosch et al, 2010;Fliszkiewicz et al, 2012;Wasielewski et al, 2013). Amongst the social bees, honey bees (Apis mellifera Linnaeus) show certain behavioral adaptations for surviving low temperatures, e.g., the storage of honey, the decrease or complete absence of broods during autumn and winter, increased longevity, and reduced metabolism of the workers (Seeley, 1985).…”
Section: Why Study Diapause In Bees?mentioning
confidence: 99%